2022
DOI: 10.1021/acs.macromol.2c00867
|View full text |Cite
|
Sign up to set email alerts
|

Three Different Types of Asymmetric Polymerization of Aryl Isocyanides by Using Simple Rare-Earth Metal Trialkyl Precursors

Abstract: Three different types of asymmetric polymerization of aryl isocyanides containing helix-sense-selective polymerization of achiral aryl isocyanides with D/L-lactide as the chiral additive, asymmetric induced polymerization of chiral aryl isocyanides, and helix-sense-selective copolymerization of chiral and achiral aryl isocyanides with chiral amplification have successfully been implemented by using two kinds of achiral monocation [LnR 2 (THF) n ] + or dication species [LnR(THF) n ] 2+ in situ generated from tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…[15][16][17][18][19][20][21][22] Several studies have reported the enantioselective and helix sense-selective polymerization initiated by chiral catalysts recently. [23][24][25][26][27][28] Polyisocyanide, one of the representative static helical polymers, has been studied extensively because of the static helix in its main chain. [29][30][31][32] Although several studies have reported the living and controlled polymerization of isocyanide, the challenge of building a new strategy for adjusting enantioselectivity and helix-sense selectivity during polymerization still remains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19][20][21][22] Several studies have reported the enantioselective and helix sense-selective polymerization initiated by chiral catalysts recently. [23][24][25][26][27][28] Polyisocyanide, one of the representative static helical polymers, has been studied extensively because of the static helix in its main chain. [29][30][31][32] Although several studies have reported the living and controlled polymerization of isocyanide, the challenge of building a new strategy for adjusting enantioselectivity and helix-sense selectivity during polymerization still remains.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, helical polymers can be obtained via the asymmetric polymerization of chiral or nonracemic monomers and the helix sense‐selective polymerization of achiral monomers under various chiral sources, such as chiral initiators, solvents, or additives [15–22] . Several studies have reported the enantioselective and helix sense‐selective polymerization initiated by chiral catalysts recently [23–28] . Polyisocyanide, one of the representative static helical polymers, has been studied extensively because of the static helix in its main chain [29–32] .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Highly ordered chiral polymers can be expressed as helical polymers, and most artificial helical polymers are prepared using asymmetric polymerizations, which provide one-handed helicity, from achiral monomers and chiral catalysts or initiators to form a stereocontrolled covalent linkage. [7][8][9][10][11][12][13][14][15][16][17] Preparation of chiral monomer is not easy. Previous work mostly relied on the chiral pool approach, which generally provides one enantiomer.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by nature, the synthesis of chiral polymers has attracted considerable research attention in polymer science for developing pathways for synthesizing chiral polymers and for applications, such as the separation of enantiomers, asymmetric catalysis, crystallization of liquids, and generation of circularly polarized light (CPL) [1–6] . Highly ordered chiral polymers can be expressed as helical polymers, and most artificial helical polymers are prepared using asymmetric polymerizations, which provide one‐handed helicity, from achiral monomers and chiral catalysts or initiators to form a stereocontrolled covalent linkage [7–17] . Preparation of chiral monomer is not easy.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Highly ordered chiral polymers can be expressed as helical polymers, and most artificial helical polymers are prepared using asymmetric polymerizations, which provide one-handed helicity, from achiral monomers and chiral catalysts or initiators to form a stereocontrolled covalent linkage. [7][8][9][10][11][12][13][14][15][16][17] Preparation of chiral monomer is not easy. Previous work mostly relied on the chiral pool approach, which generally provides one enantiomer.…”
Section: Introductionmentioning
confidence: 99%